Primary Brainstem Lymphoma: A Population-Based Study - Chen, Junyu; Cen, Bo; Hu, Fei; Qiu, Yong; Xiao, Guomin; Zhou, Junge; Ma, Xiujian; Zhang, Fangcheng (Frontiers in Surgery, 2022)
Background. Primary brainstem lymphoma (PBSL) is rare and malignant. Understanding of this disease is lacking. We aimed to characterize clinical features, estimate survival and explore survival-related factors of PBSL. Methods. Patients with a histological diagnosis of primary lymphoma in the brainstem (C71.7) from 1975 to 2016 were retrieved from Surveillance, Epidemiology, and End Results (SEER) program. Log-rank tests, univariate and multivariate Cox proportional hazard analyses were used to identify survival-related factors. Results. PBSL constituted 2.7% of brainstem malignancies. The median age of the PBSL pa-tients were 59.5 years. Diffuse large B cell lymphoma (n = 49, 84.5%) was the most prevalent histology among the 58 cases with reported specific lymphoma subtype. The majority of PBSLs were localized (n = 46, 52.3%), at low Ann Arbor Stage (I/II, n = 63, 70.5%), and presented as a single primary (n = 71, 80.7%). Chemotherapy was applied in 50 (56.8%) cases. Three-year overall survival (OS) and disease-specific survival (DSS) rates were 42.7% and 53.5%, respec-tively. Multivariate analyses showed that independent predictive/prognostic factors for OS were age (P = 0.004), tumor number (P = 0.029), and chemotherapy (P = 0.001); DSS-related fac-tors only included age (P = 0.014) and chemotherapy (P = 0.008). Conclusions. We estimated survival rates for PBSL patients. Factors associated with OS and DSS were also identified. Our findings addressed the importance of chemotherapy in treating PBSL patients.